Improvement of the methodology of analysis of the thermomechanical curves of textile materials - Челишева, Світлана Вікторівна; Рябчиков, Микола Львович (Eastern-European Journal of Enterprise Technologies, 2013)
The article is devoted to the problem of development of methodology and conduction of experiments to determine the thermomechanical properties of synthetic materials, and to develop the science-based recommendations for the determination of the parameters of the wet-heat treatment of these materials. The article considers the theoretical foundations of the wet-heat treatment in terms of achievement by a textile material of certain modes of deformation when heated. The materials for light industry products have a complex chemical structure. Despite this fact, the thermomechanical tests permit to determine the temperature range, in which the change of the properties does not lead to the loss of technological and operational characteristics of the material. The essence of the thermomechanical tests lies in determination of the deformation of the sample of the material when changing its temperature with a constant speed. In thermomechanical testing the samples are exposed to various deformations, such as stretching, compression, bending, periodical or constant action of mechanical force. Knowledge of real characteristics of the textile materials provides correct identification of the technological modes of their processing, improvement of the quality and reduction of energy consumption. For the thermomechanical testing of the materials we have developed the methodology and constructed a setting that allowed the thermomechanical tests of the materials at temperatures ranging from 20 to 300° C under uniaxial stretching. On the basis of the studies and the data obtained we have constructed the diagrams of changes of deformation and temperature of a sample during the thermomechanical test. The characteristics of the wet-heat treatment of materials were determined, and the analytical model of deformation was created.